The political development in Sri Lanka after civil war ended: a critical review for after Zarb-e-Azb operation in Pakistan - Taha Shabbir; Kehkashan Naz (International Journal of Humanities and Innovation (IJHI), 2021)
The Sri Lankan civil war began in 1983 and lasted until 2009. The tension stems from Sri Lanka's colonial period and subsequent postcolonial policies that harmed the Tamil people. Without viable alternatives, a part of the Tamil population resorted to the degree of brutality that precipitated a second civil war. Regional, domestic, and global attempts to bring the war to a halt have been futile, though some more local measures have been active. A ruthless military campaign brought the conflict to an end. However, nothing has been done in the aftermath of the war to try to resolve the civil war, including its roots. Sri Lanka's civil war exemplifies the uncertain existence of civil war resolution. With this in mind, the war's conclusion was unquestionably the product of a strategic triumph. However, the civil war should have ended; a unique constellation of structural, state, and national forces collaborated to allow for unrestricted military aggression. As long as the dominant forces, including the United States and significant European countries, understood that enough bloodshed had happened, the country's aggression could be brought to a stop. China and India, with India abstaining, voted to support the Sri Lankan government in its major offensive against insurgents. Internationally, the newly restored government used the full might of the forces against the rebels. As a consequence, those variables are deemed unusable in other situations. Tamil-Sinhala rivalry stretches all the way back to Sri Lanka's colonial period. The Tamil community took advantage of numerous market opportunities under British rule, which lasted from 1815 to 1948.